â€œFantasy Ladiesâ€: Female Performers and Actresses in Qurratulain Hyderâ€™s â€œThe Missing Photographâ€ - Bhatia, University of Western Ontario, Canada, Nandi (Asiatic: IIUM Journal of English Language and Literature, 2016)
This essay examines Qurratulain Hyderâ€™s short story â€œThe Missing Photograph,â€ as a site that interrupts what Priti Ramamurthy identifies as the relative silence of feminist and film historiography on the role and contribution of actresses in early Hindi cinema, a silence that is attributed to the fact that they did not fit the dominant paradigm of social reform, nationalism, or radical movements. By providing an acute awareness of multiple and intersecting social forces that impacted the lives of actresses, â€œThe Missing Photograph,â€ I suggest, is an important imaginative fragment that highlights how actresses, while remaining invisible, were central to the early film industry.